Elevated Serum HMGB1 Levels and Their Association with Recurrence of Acute Ischaemic Stroke - Shen L; Yang J; Zhu Z; Li W; Cui J; Gu L (Dove Medical Press, 2024)
Liping Shen, Jiangsheng Yang, Zufu Zhu, Weizhang Li, Junyou Cui, Lingyun Gu Department of Neurology, Jiangyin Hospital Affiliated to Nantong University, Jiangyin, Jiangsu, People's Republic of ChinaCorrespondence: Lingyun Gu, Department of Neurology, Jiangyin Hospital Affiliated to Nantong University, 163 Shoushan Road, Jiangyin, Jiangsu, 214400, People's Republic of China, Tel/Fax +86 13915313817, Email lygneuro@163.comPurpose: The study aimed to investigate the correlation between baseline serum levels of high mobility group box 1 (HMGB1) and the recurrence of acute ischemic stroke (AIS).Patients and Methods: A total of 544 AIS patients were enrolled and followed up monthly. Serum HMGB1 levels were measured using enzyme-linked immunosorbent assay (ELISA). The primary endpoint was the first recurrence of AIS.Results: During a median follow-up period of 43 months, 62 of the 544 AIS patients experienced a recurrence. Both HMGB1 levels and national institute of health stroke scale (NIHSS) scores were significantly higher in the recurrence group compared to the no-recurrence group (p< 0.05). According to the receiver operating characteristic curve analysis, the combination (0.855, 95% CI: 0.800- 0.911) of HMGB1 (0.745, 95% CI: 0.663- 0.826) and NIHSS (0.822, 95% CI: 0.758- 0.886) had a higher value for predicting AIS recurrence than either of them (p< 0.05). Kaplan-Meier analyses demonstrated that the cumulative survival without AIS recurrence was significantly lower in patients in the high HMGB1 level group than in the low HMGB1 level group (p< 0.05). The multifactorial Cox analyses indicated that elevated baseline serum HMGB1 levels (HR: 7.489, 95% CI:4.383- 12.795) were a highly effective predictor of recurrence in AIS.Conclusion: Elevated baseline serum HMGB1 levels were found to be a highly effective predictor of recurrence in AIS.Keywords: high mobility group box 1, acute ischemic stroke, recurrence